Asymptotic ruin probabilities for a bidimensional risk model with heavy-tailed claims and non-stationary arrivals. Issue 24 (17th December 2019) - Fu, Ke-Ang; Li, Jie
Abstract: This article studies a bidimensional risk model, in which an insurer simultaneously confronts two kinds of claims sharing a common non-stationary arrival process. Assuming that the arrival process satisfies a large deviation principle and the claim-size distributions are heavy tailed, an asymptotic formula for the corresponding ruin probability of this bidimensional risk model is obtained.